Attitudes toward end-of-life care and advance directives: a prospective survey in a family medicine clinic, Bangkok, Thailand - Manomaipiboon, Basmon; Wongvitvichot, Suttipat; Sumanasrethakul, Chavanant; Sutjakul, Benjarat; Anantanupong, Olan; Sae-tang, Siam; Sutthimethakorn, Suchitra (Chulalongkorn Medical Journal, 2023)
Background: Advance directives (ADs) have long been legalized and advocated, still few patients complete ADs in Thailand. In our setting, advance directive information will be provided to interested patients and palliative care patients. Objectives: This study examined the attitude toward end-of-life care and ADs, the prevalence of ADs completion and identified the factors associated with advance care planning among patients who attended a family medicine clinic, Faculty of Medicine, Vajira Hospital, Navamindhradhiraj university, Bangkok, Thailand. Methods: A total of 300 subjects completed a self-administered structured questionnaire, including sociodemographic factors, individuals’ health status, healthcare experiences, and other factors influencing advance care planning. Results: The overall mean age was 52.0 ± 17.7 years; 71.0% were female. Only 20.0% received information regarding ADs, and 3.0% completed ADs. Surprisingly, more than 70.0% were interested in receiving more information regarding ADs. Adjusting for other variables, acceptance of ADs was significantly associated with the female gender, education level, both secondary school completion and a university degree or higher, and experience in caring for chronically ill relatives. Conclusion: Our findings showed that an extremely low percentage of subjects completed ADs, as most had never heard of them. They were eager to obtain more information and considered it essential knowledge. This knowledge gap could guide policy planners to formulate strategies and implement advance care planning.